Students' Perception toward Implementation in Teaching Strategy of Translation - Jusmin HJ Wahid; Nurlaily Sofyan; Suhaira Do Karim (Universitas Pendidikan Mandalika, 2022)
Teaching is one of the absolute requirements or obligations for a teacher where they convey knowledge to students. One of the teachings in this research is felt in the blank strategy because the strategy helps the students to overcome the problem of translation competence. The translation is a transfer of ideas from the source language to the target language and has the same meaning. Thus translation is also very important for students to learn through the teaching process carried out by lecturers to get more information and understand the text. This research is a qualitative method. Then the research instruments used questionnaires and interviews. The total respondents are 30 English department students at the Muhammadiyah University of North Maluku. Based on the result, most of the students are enjoyable and helpful in lecturing the teaching strategy. It proved that students learn translation because it is fun for them and makes it easier to interpret words and sentences. Students who learn translation can help them organize the meaning systematically and improve their knowledge, especially vocabulary, understanding the point of view of the text, and understanding the meaning of the text. It means that the implementation of the teaching strategy in translation class was accepted and improved on students' translation competence. While the data from the interview in this study also showed that students were very enjoyable in learning translation subjects so that they can improve their understanding of the meaning of a text, competence in translating a text, and improve their competence in understanding of English text.